Dialogue without barriers. A comprehensive approach to dealing with stuttering - Sønsterud, Hilda; Wesierska, Katarzyna (Agere Aude, 2023)
The book Dialogue without barriers: A comprehensive approach to dealing with stuttering is the result of Norwegian-Polish cooperation undertaken in the project LOGOLab – Dialogue without barriers. Three partners have been involved in the production of this book, namely, the University of Silesia in Katowice, Poland, the UiT Arctic University of Norway in Tromsø, and the Agere Aude Foundation for Knowledge and Social Dialogue. The project was implemented under the Education Program financed by the EEA Grants (EEA / 19 / K1 / D1 / W / 0031). The EEA Grants represent the contribution of Iceland, Liechtenstein, and Norway towards a green, competitive, and inclusive Europe. The most important goal of the LOGOLab project was to raise the standards of speech-language therapy in stuttering by incorporating the principles of Evidence-based practice, taking into account the assumptions of inclusive education and community-based model of intervention. An essential strategy for achieving this goal has become the dissemination of reliable and up-to-date knowledge about stuttering, and the development of appropriate social attitudes towards stuttering. The improvement of the quality of academic education for speech-language therapy students and of vocational training for certified speech-language therapists should also be mentioned. An additional aim was to provide reliable information for leaders of the self-help movement, who support people with stuttering non-institutionally.